Use of psychedelic treatments in psychiatric clinical practice: an EPA policy paper - M. Destoop; P. Mohr; F. Butlen; P. Kéri; J. Samochowiec; L. De Picker; A. Fiorillo; K.P.C. Kuypers; G. Dom (European Psychiatry)
Abstract